2017
DOI: 10.1007/s13258-017-0640-6
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping and candidate gene analysis of the quantitative trait locus gw8.1 associated with grain length in rice

Abstract: A quantitative trait locus (QTL) gw8.1 was detected in the population derived from a cross between the elite japonica cultivar, 'Hwaseong' and Oryza rufipogon (IRGC 105491). Near isogenic lines (NILs) harboring the O. rufipogon segment on chromosome 8 showed increased grain length and weight compared to those of the recurrent parent, Hwaseong. This QTL was mapped to a 175.3-kb region containing 28 genes, of which four were considered as candidates based on the presence of mutations in their coding regions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…It is of great significance to clone the genes controlling grain weight and then to clarify their molecular genetic mechanism. Great achievements have been made in genes/QTLs identification and dissection for grain size and grain weight in many crops, such as rice 1620 , soybean 21,22 , wheat 23,24 . Especially many genes related to grain weight or grain size in rice, including GS3 25 , GS5 16 , qGL3 26 , GW2 18 , GW8 27 , GS2 28 , qGW7/GL7 29 , have been successfully cloned.…”
Section: Introductionmentioning
confidence: 99%
“…It is of great significance to clone the genes controlling grain weight and then to clarify their molecular genetic mechanism. Great achievements have been made in genes/QTLs identification and dissection for grain size and grain weight in many crops, such as rice 1620 , soybean 21,22 , wheat 23,24 . Especially many genes related to grain weight or grain size in rice, including GS3 25 , GS5 16 , qGL3 26 , GW2 18 , GW8 27 , GS2 28 , qGW7/GL7 29 , have been successfully cloned.…”
Section: Introductionmentioning
confidence: 99%
“…In monocotyledonous endospermic seeds such as rice, the formation of grain size, and weight is largely determined by the development of endosperm and the spikelet hull. For example, the key genes GS5 and GW8 have been identified as critical regulators for controlling grain width and weight through regulating cell number during seed development; while the regulators GL7 and SPL13 determine rice grain size through the regulation of cell size [48,49,50,51]. In dicotyledonous non-endospermic seeds such as Arabidopsis, the formation of seed size and weight is usually determined by the development of cotyledon.…”
Section: Discussionmentioning
confidence: 99%
“…The GW8 bearing genotypes were reported to have a higher grain length and grain length-width ratio [20]. The scanning results of the electron microscopy analysis of the lemma in GW8 .1 carrying NILs showed that the inner epidermal cell length was higher than the lines without this gene, indicating that GW8 .1 might be responsible for regulating cell elongation [64]. GW8 (OsSPL16) encodes a protein that is positively associated with cell proliferation [31].…”
Section: Discussionmentioning
confidence: 99%